2008
DOI: 10.1007/s00705-008-0048-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of infectious particles of grass carp reovirus by treatment with proteases

Abstract: Proteolytic cleavages play an important role in reovirus infection during entry into cells. The effects of protease digestion on the morphology, infectivity and polypeptide composition of grass carp reovirus (GCRV) were investigated. Following treatment with chymotrypsin, the different subviral particles of GCRV were isolated using density gradient centrifugation and examined by electron microscope (EM). Analysis of protein components revealed that the viral outer capsid was composed of VP5 and VP7. Of particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…Recent studies on the GCRV genome and 3D structure have revealed that the VP5 and VP7 proteins comprise the outer capsid shell of the virus, and resemble the outer capsid proteins 1 and σ3 of MRV, respectively, such that VP5 and VP7 in GCRV might play critical roles during virus entry into cells [25][26][27]. VP7, located outward at icosahedral positions through its close interactions with underlying VP5 subunits, is the major surface protein of GCRV virions, and is recognized to provide stability for the virion or VP5 protein [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on the GCRV genome and 3D structure have revealed that the VP5 and VP7 proteins comprise the outer capsid shell of the virus, and resemble the outer capsid proteins 1 and σ3 of MRV, respectively, such that VP5 and VP7 in GCRV might play critical roles during virus entry into cells [25][26][27]. VP7, located outward at icosahedral positions through its close interactions with underlying VP5 subunits, is the major surface protein of GCRV virions, and is recognized to provide stability for the virion or VP5 protein [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, GCRV lacks a counterpart to the MRV 1 protein, which functions as the cell attachment protein situated on each fivefold vertex [11], so the VP7 protein might play a key role in interacting with the host cell during virus infection. An earlier study indicated that the complete digestion of VP7 and partial cleavage of VP5 leads to enhanced infectivity, suggesting that VP7 and VP5 may cooperate with each other for cell entry during viral infection [25]. Moreover, amongst all seven structural proteins of GCRV, the VP7 capsid protein is the most divergent based on genome sequence and single particle Cryo-EM image analyses, suggesting that VP7 is a more specific antigen than the other GCRV proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCRV-873 virus samples were subjected to a series of 10-fold serial dilutions in MEM (mininum essential medium) for titer determination. Plaque assays were done by determining the plaque forming unit (PFU) value per milliliter according to the method indicated before [13], and the relative infectivity of different particles was also measured using endpoint experiments by calculating the 50% tissue culture infective dose (TCID 50 ) as described previously [12,25]. Four original antisera samples induced by EBY100, EBY100-VP7, EBY∆M1-VP7, and EBY∆M9-VP7 were filtered, respectively.…”
Section: Neutralization Assay Of Prepared Antibodiesmentioning
confidence: 99%
“…Like many other reoviruses, GCRV is a multilayered spherically structured particle that contains a genome of 11 segments of dsRNA (named S1-S11) that encode 7 structural proteins (VP1-VP7) and 5 nonstructural proteins (Attoui et al, 2002;Fang et al, 2005Fang et al, , 2008Cheng et al, 2008Cheng et al, , 2009). …”
Section: Introductionmentioning
confidence: 99%